The Use of Information Technology in Solving Problems in Mathematics Lessons in Elementary School - Jonpo’latovna, Saidova Mohinur; Komilqizi, Karimova Kamola (European Journal of Life Safety and Stability (2660-9630), 2021)
This article discusses the issues of increasing the effectiveness of students' participation in mathematics lessons using information technology, the formation and strengthening of their knowledge and skills in modern technology.